Manufacturing method of hydrogen fuel cell monomer and hydrogen fuel cell stack
By adopting chemical crosslinked sulfonated polyimide film, platinum-ruthenium palladium ternary alloy catalyst and multi-layer composite membrane electrode structure in hydrogen fuel cell monomers, the problems of proton conduction efficiency, mechanical strength, catalytic activity and gas diffusion efficiency of traditional hydrogen fuel cell monomers are solved, and higher energy density and long-term stability are achieved.
Patent Information
- Application Number
- CN202510127926.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-05
- Publication Date
- 2025-04-22
AI Technical Summary
Traditional hydrogen fuel cell monomers face problems such as low proton conduction efficiency, insufficient mechanical strength, insufficient catalytic activity and low gas diffusion efficiency in the design of proton conductive films, catalysts and electrode structures, resulting in insufficient battery energy density and long-term stability.
The sulfonated polyimide film is used as the proton conductive film, and its mechanical strength is enhanced by chemical cross-linking treatment; a platinum-ruthenium palladium ternary alloy catalyst is used, and the catalyst ink is formed through jet deposition technology; a multi-layer graphene nanosheet layer and microporous carbon paper with nanofiber structure are bonded to the surface of the catalytic layer to form a multi-layer composite film electrode.
It significantly improves the proton conduction efficiency, mechanical strength, catalytic performance and gas diffusion efficiency of hydrogen fuel cells, extends the service life of the battery, and improves the energy density and reaction rate, so that the battery still maintains excellent output performance under high intensity and long-term operation.
Smart Images

Figure CN119864460A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen fuel cells, and in particular to a method for manufacturing a hydrogen fuel cell monomer and a hydrogen fuel cell stack. Background Art
[0002] Hydrogen battery monomer preparation technology is a key technology developed based on the efficient use of hydrogen energy and its environmentally friendly characteristics. Hydrogen batteries, especially fuel cells, generate electricity by reacting hydrogen and oxygen, and only produce water as a byproduct, with the significant advantage of zero emissions. In the preparation process, advanced electrochemical principles are usually used to design a battery structure including an anode, a cathode and an electrolyte. Hydrogen reacts with the electrolyte at the anode, and the released electrons flow to the cathode through an external circuit, combining with oxygen to generate water, while releasing electricity.
[0003] In the manufacturing method of traditional hydrogen fuel cell monomers, the design of proton conduction membranes, catalysts and electrode structures faces significant challenges. The materials and processes of proton conduction membranes limit their proton conduction efficiency and mechanical strength, which in turn affects the energy density and long-term stability of the battery. The composition and preparation process of the catalyst often lead to insufficient catalytic activity, affecting the reaction rate and efficiency of the battery. At the same time, the electrode structure, especially the combination of the gas diffusion layer and the catalyst layer, limits the effective diffusion of the gas and the durability of the electrode, causing the battery to perform more rapidly under high-intensity and long-term operation. For this reason, a manufacturing method for hydrogen fuel cell monomers and hydrogen fuel cell stacks is proposed. Summary of the invention
[0004] In view of the deficiencies of the prior art, the present invention provides a method for manufacturing a hydrogen fuel cell monomer and a hydrogen fuel cell stack to solve the background technical problems.
[0005] In the first aspect, to achieve the above-mentioned purpose, the present invention provides the following technical solution: a method for manufacturing a hydrogen fuel cell monomer, comprising the following steps: S1: Sulfonated polyimide membrane is used as the proton conducting membrane; S2: preparing a platinum-ruthenium-palladium ternary alloy catalyst by using a platinum salt, a ruthenium salt and a palladium salt in a molar ratio of 1:1:0.1 to 3:1:0.5; S3: dispersing the platinum-ruthenium-palladium ternary alloy catalyst prepared in S2 in a solution containing a proton-conducting polymer to form a catalyst ink, and uniformly coating the catalyst ink on both sides of the proton-conducting membrane by a deposition technique to form a catalytic layer; S4: laminating a multi-layer graphene nanosheet layer on the surface of the catalyst layer by hot pressing technology; laminating a microporous carbon paper on the surface of the multi-layer graphene nanosheet layer by hot pressing technology; Based on the preparation of S1, S2, S3 and S4, a multilayer composite membrane electrode is formed; S5: Titanium or titanium alloy is selected as the bipolar plate material, the multi-layer composite membrane electrode is placed between the two bipolar plates, a sealant is coated on the contact surface between the bipolar plate and the multi-layer composite membrane, and the bipolar plate and the multi-layer composite membrane are welded and fixed by welding technology to form a hydrogen fuel cell monomer.
[0006] Preferably, the sulfonated polyimide membrane is further chemically treated, and the specific preparation includes: The sulfonated polyimide membrane is immersed in a solution containing a cross-linking agent, wherein the cross-linking agent is an organic compound containing multiple active functional groups; The heat treatment is performed at a temperature of 80° C. to 120° C. for 2 to 4 hours to allow the cross-linking agent to chemically react with the sulfonated polyimide membrane to form a chemical cross-linking structure, thereby enhancing the mechanical strength and chemical stability of the membrane.
[0007] Preferably, the platinum ruthenium palladium ternary alloy catalyst is specifically prepared by: Dissolve the platinum salt, the ruthenium salt and the palladium salt in an organic solvent according to the molar ratio in S2; Under the protection of an inert gas, the solution is heated to 200° C. to 300° C. to reduce the metal salt to metal nanoparticles to form a platinum-ruthenium alloy catalyst; The pure platinum-ruthenium alloy catalyst was obtained by centrifugation and washing.
[0008] Preferably, the hot pressing conditions of the multilayer graphene nanosheets and microporous carbon paper are as follows: the hot pressing temperature is 150°C to 200°C, the pressure is 5 to 10 MPa, the time is 1 to 5 minutes, and inert gas protection is used during the hot pressing process.
[0009] Preferably, the average particle size of the platinum-ruthenium-palladium ternary alloy catalyst is 3 nanometers, and the catalyst loading is 1 mg / cm².
[0010] Preferably, the catalyst ink is coated on both sides of the proton conducting membrane using a spray deposition technique to form a thin and uniform catalyst layer.
[0011] Preferably, the microporous carbon paper is carbon paper with a nanofiber structure to improve gas diffusion efficiency and electrode durability.
[0012] In a second aspect, a method for manufacturing a hydrogen fuel cell stack comprises the following steps: A hydrogen fuel cell monomer is prepared based on the manufacturing method of the hydrogen fuel cell monomer described in the first aspect, and the hydrogen fuel cell monomers are arranged in series to form a monomer array; Stainless steel or titanium alloy is selected as the gas distribution plate material, aluminum alloy or copper alloy is selected as the cooling plate material, and the monomer array, gas distribution plate and cooling plate components are assembled into a hydrogen fuel cell stack in a predetermined order.
[0013] Compared with the prior art, the present invention has the following beneficial effects: The present invention adopts sulfonated polyimide membrane as proton conduction membrane and chemically treats the sulfonated polyimide membrane, which not only significantly enhances its mechanical strength and chemical stability, but also effectively prolongs the overall service life of the battery, providing a strong guarantee for the long-term stable operation of hydrogen fuel cells; at the same time, a platinum ruthenium palladium ternary alloy catalyst is introduced to improve the catalytic performance, greatly improve the energy density and reaction rate of the battery, so that the hydrogen fuel cell performs well in power output and response speed; in addition, the introduction of multi-layer graphene nanosheets and microporous carbon paper with nanofiber structure into the electrode structure further optimizes the gas diffusion path, significantly improves the gas diffusion efficiency, and enhances the durability of the electrode. The stability of the battery is improved, and the hydrogen fuel cell can still maintain excellent output performance under long-term and high-intensity operation, thereby improving the performance of the hydrogen fuel cell.
[0014] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a flow chart of the method for manufacturing a hydrogen fuel cell monomer of the present invention; Figure 2 The present invention is a flow chart of the method for manufacturing a hydrogen fuel cell stack. DETAILED DESCRIPTION
[0016] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this technical field without creative work are within the scope of protection of the present invention.
[0017] Example 1 This embodiment provides a method for manufacturing a hydrogen fuel cell monomer, which specifically includes the following steps: Step 1: Manufacturing of hydrogen fuel cell monomers Preparation of proton conducting membrane: Sulfonated polyimide membrane was selected as the proton conducting membrane, which has high proton conductivity and good mechanical strength. Furthermore, the sulfonated polyimide membrane was immersed in a dimethyl sulfoxide (DMSO) solution containing a cross-linking agent for 4 hours, and the cross-linking agent was polyethylene glycol diglycidyl ether containing multiple active functional groups. It was then heat treated at 110°C for 3.5 hours to form a stable chemical cross-linking structure to enhance the durability and chemical stability of the membrane.
[0018] Step 2: Catalyst preparation: Platinum salt, ruthenium salt and palladium salt are dissolved in ethylene glycol in a molar ratio of 2:2:0.3 by wet chemical reduction. Under the protection of inert gas (argon), the solution is heated to 275°C for 2 hours to fully reduce the metal salt to metal nanoparticles to form a platinum ruthenium palladium ternary alloy catalyst. The residual solvent and impurities are removed by centrifugation and multiple washing to obtain a pure and evenly dispersed catalyst powder with an average particle size of 3 nanometers and a loading amount of 1.2 mg / cm² to ensure the best catalytic efficiency.
[0019] Step 3: Formation of the catalytic layer: Disperse the above-mentioned platinum, ruthenium, palladium ternary alloy catalyst powder in an ethanol solution containing a proton-conducting polymer (such as sulfonated polystyrene) to form a high-concentration catalyst ink; use jet deposition technology to evenly coat the ink on both sides of the proton-conducting membrane to form a thin and uniform catalytic layer with a thickness controlled at about 50 nanometers.
[0020] Step 4: Preparation of multilayer composite membrane electrode: On the surface of the catalyst layer, multilayer graphene nanosheets are bonded by hot pressing technology, with a hot pressing temperature of 180°C, a pressure of 8MPa, and a time of 2.5 minutes to ensure good interface bonding and conductivity. Subsequently, microporous carbon paper with a nanofiber structure is bonded on the surface of the multilayer graphene nanosheet. The carbon paper is prepared by electrospinning and has extremely high gas diffusion efficiency and electrode durability.
[0021] Step 5: Assembly of hydrogen fuel cell monomer: Titanium alloy is selected as the bipolar plate material, which has excellent conductivity and corrosion resistance. The multi-layer composite membrane electrode is precisely placed between the two bipolar plates, and the edge is sealed with sealant to ensure the isolation of gas and electrolyte. Finally, laser welding technology is used to firmly weld the bipolar plate and the multi-layer composite membrane together to form a hydrogen fuel cell monomer with a compact structure and good sealing.
[0022] Example 2 This embodiment provides a method for manufacturing a hydrogen fuel cell monomer, which specifically includes the following steps: Step 1: Manufacturing of hydrogen fuel cell monomers Preparation of proton conducting membrane: Sulfonated polyimide membrane was selected as the proton conducting membrane, which has high proton conductivity and good mechanical strength. Furthermore, the sulfonated polyimide membrane was immersed in a dimethyl sulfoxide (DMSO) solution containing a cross-linking agent for 4 hours, and the cross-linking agent was polyethylene glycol diglycidyl ether containing multiple active functional groups. It was then heat treated at 110°C for 3.5 hours to form a stable chemical cross-linking structure to enhance the durability and chemical stability of the membrane.
[0023] Step 2: Catalyst preparation: Platinum salt, ruthenium salt and palladium salt are dissolved in ethylene glycol at a molar ratio of 1.5:1.5:0.2 by wet chemical reduction. Under the protection of inert gas (argon), the solution is heated to 275°C for 2 hours to fully reduce the metal salts to metal nanoparticles to form a platinum ruthenium palladium ternary alloy catalyst. The residual solvent and impurities are removed by centrifugation and multiple washings to obtain a pure and evenly dispersed catalyst powder with an average particle size of 3 nanometers and a loading amount of 0.8 mg / cm² to ensure the best catalytic efficiency.
[0024] Step 3: Formation of the catalytic layer: Disperse the above-mentioned platinum, ruthenium, palladium ternary alloy catalyst powder in an ethanol solution containing a proton-conducting polymer (such as sulfonated polystyrene) to form a high-concentration catalyst ink; use jet deposition technology to evenly coat the ink on both sides of the proton-conducting membrane to form a thin and uniform catalytic layer with a thickness controlled at about 50 nanometers.
[0025] Step 4: Preparation of multilayer composite membrane electrode: On the surface of the catalyst layer, multilayer graphene nanosheets are bonded by hot pressing technology, with a hot pressing temperature of 160°C, a pressure of 10MPa, and a time of 2.5 minutes to ensure good interface bonding and conductivity. Subsequently, microporous carbon paper with a nanofiber structure is bonded on the surface of the multilayer graphene nanosheet. The carbon paper is prepared by electrospinning and has extremely high gas diffusion efficiency and electrode durability.
[0026] Step 5: Assembly of hydrogen fuel cell monomer: Titanium alloy is selected as the bipolar plate material, which has excellent conductivity and corrosion resistance. The multi-layer composite membrane electrode is precisely placed between the two bipolar plates, and the edge is sealed with sealant to ensure the isolation of gas and electrolyte. Finally, laser welding technology is used to firmly weld the bipolar plate and the multi-layer composite membrane together to form a hydrogen fuel cell monomer with a compact structure and good sealing.
[0027] Example 3 This embodiment provides a method for manufacturing a hydrogen fuel cell monomer, which specifically includes the following steps: Step 1: Manufacturing of hydrogen fuel cell monomers Preparation of proton conducting membrane: Sulfonated polyimide membrane is selected as the proton conducting membrane, which has high proton conductivity and good mechanical strength.
[0028] Step 2: Catalyst preparation: Platinum salt and ruthenium salt are dissolved in ethylene glycol at a molar ratio of 2:1 by wet chemical reduction. Under the protection of inert gas (argon), the solution is heated to 275°C for 2 hours to fully reduce the metal salt to metal nanoparticles to form a platinum-ruthenium binary alloy catalyst. The residual solvent and impurities are removed by centrifugation and multiple washings to obtain a pure and evenly dispersed catalyst powder with an average particle size of 3 nanometers and a loading amount of 0.8 mg / cm² to ensure the best catalytic efficiency.
[0029] Step 3: Formation of catalytic layer: Disperse the above-mentioned platinum-ruthenium binary alloy catalyst powder in an ethanol solution containing a proton-conducting polymer (such as sulfonated polystyrene) to form a high-concentration catalyst ink; use jet deposition technology to evenly coat the ink on both sides of the proton-conducting membrane to form a thin and uniform catalytic layer with a thickness controlled at about 50 nanometers.
[0030] Step 4: Preparation of multilayer composite membrane electrode: On the surface of the catalyst layer, multilayer graphene nanosheets are laminated by hot pressing technology at a temperature of 160°C, a pressure of 10 MPa, and a time of 2.5 minutes to ensure good interface bonding and conductivity. Subsequently, carbon paper is laminated on the surface of the multilayer graphene nanosheets.
[0031] Step 5: Assembly of hydrogen fuel cell monomer: Titanium alloy is selected as the bipolar plate material, which has excellent conductivity and corrosion resistance. The multi-layer composite membrane electrode is precisely placed between the two bipolar plates, and the edge is sealed with sealant to ensure the isolation of gas and electrolyte. Finally, laser welding technology is used to firmly weld the bipolar plate and the multi-layer composite membrane together to form a hydrogen fuel cell monomer with a compact structure and good sealing.
[0032] Comparative Example 1 Step 1: Manufacturing of hydrogen fuel cell monomers Preparation of proton conducting membrane: Nafion is selected as the proton conducting membrane, which has high proton conductivity and good mechanical strength.
[0033] Step 2: Catalyst preparation: Platinum, ruthenium and palladium salts were prepared by electrodeposition at a molar ratio of 2:2:0.3 to form a platinum-ruthenium-palladium ternary alloy catalyst. The residual solvent and impurities were removed by centrifugation and multiple washings to obtain a pure and evenly dispersed catalyst powder with an average particle size of 3 nanometers and a loading of 1.2 mg / cm² to ensure optimal catalytic efficiency.
[0034] Step 3: Formation of the catalytic layer: Disperse the above-mentioned platinum, ruthenium, palladium ternary alloy catalyst powder in an ethanol solution containing a proton conducting polymer (such as sulfonated polystyrene) to form a catalyst ink; use jet deposition technology to evenly coat the ink on both sides of the proton conducting membrane to form a thin and uniform catalytic layer with a thickness controlled at about 50 nanometers.
[0035] Step 4: Preparation of multilayer composite membrane electrode: On the surface of the catalyst layer, multilayer graphene nanosheets are bonded by hot pressing technology, with a hot pressing temperature of 180°C, a pressure of 8MPa, and a time of 2.5 minutes to ensure good interface bonding and conductivity. Subsequently, microporous carbon paper with a nanofiber structure is bonded on the surface of the multilayer graphene nanosheet. The carbon paper is prepared by electrospinning and has extremely high gas diffusion efficiency and electrode durability.
[0036] Step 5: Assembly of hydrogen fuel cell monomer: Titanium alloy is selected as the bipolar plate material, which has excellent conductivity and corrosion resistance. The multi-layer composite membrane electrode is precisely placed between the two bipolar plates, and the edge is sealed with sealant to ensure the isolation of gas and electrolyte. Finally, laser welding technology is used to firmly weld the bipolar plate and the multi-layer composite membrane together to form a hydrogen fuel cell monomer with a compact structure and good sealing.
[0037] Comparative Example 2 Step 1: Manufacturing of hydrogen fuel cell monomers Preparation of proton conducting membrane: Perfluorosulfonic acid membrane was selected as the proton conducting membrane.
[0038] Step 2: Catalyst preparation: using platinum black catalyst.
[0039] Step 3: Formation of the catalytic layer: Disperse the above-mentioned platinum black catalyst powder in an ethanol solution containing a proton conducting polymer (such as sulfonated polystyrene) to form a catalyst ink; use jet deposition technology to evenly coat the ink on both sides of the proton conducting membrane to form a thin and uniform catalytic layer with a thickness controlled at about 50 nanometers.
[0040] Step 4: Preparation of multilayer composite membrane electrode: On the surface of the catalyst layer, multilayer graphene nanosheets are bonded by hot pressing technology, with a hot pressing temperature of 180°C, a pressure of 8MPa, and a time of 2.5 minutes to ensure good interface bonding and conductivity. Subsequently, microporous carbon paper with a nanofiber structure is bonded on the surface of the multilayer graphene nanosheet. The carbon paper is prepared by electrospinning and has extremely high gas diffusion efficiency and electrode durability.
[0041] Step 5: Assembly of hydrogen fuel cell monomer: Titanium alloy is selected as the bipolar plate material, which has excellent conductivity and corrosion resistance. The multi-layer composite membrane electrode is precisely placed between the two bipolar plates, and the edge is sealed with sealant to ensure the isolation of gas and electrolyte. Finally, laser welding technology is used to firmly weld the bipolar plate and the multi-layer composite membrane together to form a hydrogen fuel cell monomer with a compact structure and good sealing.
[0042] Comparative Example 3 Step 1: Manufacturing of hydrogen fuel cell monomers Preparation of proton conducting membrane: Perfluorosulfonic acid membrane was selected as the proton conducting membrane.
[0043] Step 2: Catalyst preparation: using platinum black catalyst.
[0044] Step 3: Formation of the catalytic layer: Disperse the above-mentioned platinum black catalyst powder in an ethanol solution containing a proton conducting polymer (such as sulfonated polystyrene) to form a high-concentration catalyst ink; use deposition technology to evenly coat the ink on both sides of the proton conducting membrane to form a thin and uniform catalytic layer with a thickness controlled at about 50 nanometers.
[0045] Step 4: Preparation of multi-layer composite membrane electrode: A carbon nanotube layer is bonded to the surface of the catalyst layer using hot pressing technology.
[0046] Step 5: Assembly of hydrogen fuel cell monomer: Titanium alloy is selected as the bipolar plate material, which has excellent conductivity and corrosion resistance. The conductive membrane electrode is placed between the two bipolar plates, and the edge is sealed with sealant to ensure the isolation of gas and electrolyte. Finally, laser welding technology is used to firmly weld the bipolar plate and the conductive membrane electrode together to form a hydrogen fuel cell monomer with a compact structure and good sealing.
[0047] The hydrogen fuel cell monomers prepared in the above-mentioned Example 1, Example 2, Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3 were tested, and the test data are shown in the following Table 1: Table 1
[0048] Effect of proton conducting membrane: Examples 1, 2, and 3 all use sulfonated polyimide membranes, and the durability and chemical stability of the membranes are enhanced by chemical cross-linking treatment. Compared with the Nafion membrane used in Comparative Example 1 and the perfluorosulfonic acid membrane used in Comparative Examples 2 and 3, they exhibit higher open circuit voltage and maximum output power density.
[0049] Chemical cross-linking treatment effectively improves the mechanical strength and proton conductivity of the proton conducting membrane, thereby improving the overall performance of the fuel cell.
[0050] Impact of catalyst: Examples 1 and 2 use a platinum-ruthenium-palladium ternary alloy catalyst, which exhibits higher catalytic efficiency and durability compared to the platinum-ruthenium binary alloy catalyst in Example 3 and the platinum black catalyst used in Comparative Examples 2 and 3.
[0051] The platinum-ruthenium-palladium ternary alloy catalyst has a more optimized electronic structure and higher catalytic activity, which helps to improve the output power density and durability of fuel cells.
[0052] The catalyst powder prepared by the wet chemical reduction method is evenly dispersed and has a small particle size, which is conducive to the formation of an efficient catalytic layer.
[0053] Influence of the catalyst layer formation method: Examples 1, 2, and 3 all use spray deposition technology to form the catalyst layer. Compared with the deposition technology used in Comparative Example 3, the spray deposition technology can more accurately control the thickness and uniformity of the catalyst layer, thereby improving the performance of the fuel cell.
[0054] Influence of multilayer composite membrane electrode: In Examples 1, 2, and 3, multiple layers of graphene nanosheets and microporous carbon paper with a nanofiber structure are bonded to the surface of the catalyst layer. Compared with only bonding a carbon nanotube layer in Comparative Example 3, the multilayer composite membrane electrode has higher conductivity and gas diffusion efficiency, which helps to improve the performance and durability of the fuel cell.
[0055] Overall performance and durability: Example 1 shows the best performance in open circuit voltage, maximum output power density and durability tests, which is due to the special treatment of the proton conducting membrane, efficient catalyst preparation, precise catalytic layer formation method and optimized multi-layer composite membrane electrode structure.
[0056] The performance of Comparative Examples 2 and 3 is relatively poor, especially the performance attenuation in the durability test is large, which may be related to the selection of the proton conducting membrane, the type of catalyst and the method of forming the catalytic layer.
[0057] In summary, the hydrogen fuel cell monomer manufacturing method provided by the present invention significantly improves the performance and durability of the fuel cell by optimizing the processing of the proton conductive membrane, the preparation of the catalyst, the formation method of the catalytic layer, and the structure of the multi-layer composite membrane electrode. Example 1 showed the best performance in all test indicators, proving the effectiveness and practicality of the present invention.
[0058] Example 4 This embodiment provides a method for manufacturing a hydrogen fuel cell stack, wherein the hydrogen fuel cell monomers manufactured according to Embodiment 1, Embodiment 2, or Embodiment 3 are arranged in series to form a monomer array; Stainless steel or titanium alloy is selected as the gas distribution plate material, aluminum alloy or copper alloy is selected as the cooling plate material, and the monomer array, gas distribution plate and cooling plate components are assembled into a hydrogen fuel cell stack in a predetermined order.
Claims
1. A method for manufacturing a hydrogen fuel cell monomer, characterized in that: The following steps are involved: S1: Sulfonated polyimide membrane is used as the proton conducting membrane; S2: preparing a platinum-ruthenium-palladium ternary alloy catalyst by using a platinum salt, a ruthenium salt and a palladium salt in a molar ratio of 1:1:0.1 to 3:1:0.5; S3: dispersing the platinum-ruthenium-palladium ternary alloy catalyst prepared in S2 in a solution containing a proton-conducting polymer to form a catalyst ink, and uniformly coating the catalyst ink on both sides of the proton-conducting membrane by a deposition technique to form a catalytic layer; S4: laminating a multi-layer graphene nanosheet layer on the surface of the catalyst layer by hot pressing technology; laminating a microporous carbon paper on the surface of the multi-layer graphene nanosheet layer by hot pressing technology; Based on the preparation of S1, S2, S3 and S4, a multilayer composite membrane electrode is formed; S5: Titanium or titanium alloy is selected as the bipolar plate material, the multi-layer composite membrane electrode is placed between the two bipolar plates, a sealant is coated on the contact surface between the bipolar plate and the multi-layer composite membrane, and the bipolar plate and the multi-layer composite membrane are welded and fixed by welding technology to form a hydrogen fuel cell monomer.
2. The method for manufacturing a hydrogen fuel cell monomer according to claim 1, characterized in that: The sulfonated polyimide membrane is also chemically treated, and the specific preparation includes: The sulfonated polyimide membrane is immersed in a solution containing a cross-linking agent, wherein the cross-linking agent is an organic compound containing multiple active functional groups; The heat treatment is performed at a temperature of 80° C. to 120° C. for 2 to 4 hours to allow the cross-linking agent to chemically react with the sulfonated polyimide membrane to form a chemical cross-linking structure, thereby enhancing the mechanical strength and chemical stability of the membrane.
3. The method for manufacturing a hydrogen fuel cell monomer according to claim 1, characterized in that: The specific preparation of the platinum-ruthenium-palladium ternary alloy catalyst includes: Dissolve the platinum salt, the ruthenium salt and the palladium salt in an organic solvent according to the molar ratio in S2; Under the protection of an inert gas, the solution is heated to 200° C. to 300° C. to reduce the metal salt to metal nanoparticles to form a platinum-ruthenium alloy catalyst; The pure platinum-ruthenium alloy catalyst was obtained by centrifugation and washing.
4. The method for manufacturing a hydrogen fuel cell monomer according to claim 1, characterized in that: The hot pressing conditions of the multi-layer graphene nanosheets and microporous carbon paper are as follows: the hot pressing temperature is 150°C to 200°C, the pressure is 5 to 10MPa, the time is 1 to 5 minutes, and inert gas protection is used during the hot pressing process.
5. The method for manufacturing a hydrogen fuel cell monomer according to claim 3, characterized in that: The average particle size of the platinum-ruthenium-palladium ternary alloy catalyst is 3 nanometers, and the catalyst loading is 1 mg / cm².
6. The method for manufacturing a hydrogen fuel cell monomer according to claim 1, characterized in that: The catalyst ink is coated on both sides of the proton conducting membrane by using a spray deposition technique to form a thin and uniform catalyst layer.
7. The method for manufacturing a hydrogen fuel cell monomer according to claim 1, characterized in that: The microporous carbon paper adopts carbon paper with a nanofiber structure, which improves the gas diffusion efficiency and the durability of the electrode.
8. A method for manufacturing a hydrogen fuel cell stack, characterized in that: The following steps are involved: A hydrogen fuel cell monomer is prepared based on the manufacturing method of the hydrogen fuel cell monomer according to claims 1 to 7 above, and the hydrogen fuel cell monomers are arranged in series to form a monomer array; Stainless steel or titanium alloy is selected as the gas distribution plate material, aluminum alloy or copper alloy is selected as the cooling plate material, and the monomer array, gas distribution plate and cooling plate components are assembled into a hydrogen fuel cell stack in a predetermined order.